Can an Authentic Assessment Task Improve the Health Behaviours of Undergraduate Students? - Jake Meincke; Kylie Gwynne; Christine L. Chiu; Alexandra J. Bhatti; Vita Christie; Jordan Janszen; Leah Nazareth; Isabella Needham; Morwenna Kirwan (MDPI AG, 2023)
Currently, more than ever, the mental and physical well-being of university students have been identified as priorities, and universities are well placed to address well-being by integrating health promotion into their courses. This study looks at the effectiveness of embedding an authentic assessment task to improve health-seeking behaviours related to sleep, stress, and nutrition into the curricula of undergraduate health-science students. Qualitative and quantitative data were gathered both pre- and post-test, and content was qualitatively analysed. The study found that students were willing and able to improve health-seeking behaviours, with a significant increase in fruit consumption. There was no reported change in stress or sleep.